THE TAXATION OF IMPUTED INCOME FROM REAL ESTATE LEASING TO PREVENT SHADOWING AND PROPERTY INEQUALITY - L. P. Koroleva (Финансы: теория и практика, 2017)
The neo-industrial development of the Russian economy requires increasing the saving raio of fixed capital. The key source of investment is the savings of households currently underutilized mostly because people prefer to invest in real estate. Real estate leasing brings a stable income which often remains in the shadow or informal economy and is not subject to taxation. The availability of such income contributes to the reduction of the labor supply by the owner, the aggravation of property inequality and the distortion of investment decisions. This makes the use of the imputed income tax on leasing real estate a matter of vital importance. In view of the above, the development of the basic structure of the tax is the purpose of the study. The paper analyzes the role of taxation of both imputed and real incomes derived from real estate leasing in the budget system of Russia for the period of 2006–2016 in the context of federal districts. The potential of the imputed taxation in the interests of reducing property inequality and legalization of personal lease incomes was estimated. Methods of the economic analysis and statistics as well as general scientific research methods and techniques were used. It is proposed to increase the tax burden on the residential lease by introducing an additional clause to Chapter 23 of the Russian Federation Tax Code establishing the procedure for taxation of the imputed income from leasing (renting) real estate owned by individuals. The key elements of the tax structure are identified. Two variants of its administration are offered. The preconditions for introducing the imputed lease tax in Russia are outlined. Recommendations on the calculation of the tax base — imputed net income — are given. The introduction of the taxation of imputed lease income will help reduce the attractiveness of real estate investment, reorient the personal savings to the financing of business activities or investing in the real sector It will also contribute to legalization of lease incomes, increasing tax revenues of regional and municipal budgets and reducing the property inequality of the population.